Walking energetics and white matter hyperintensities in mid‐to‐late adulthood - Ryan J. Dougherty; Amal A. Wanigatunga; Yang An; Qu Tian; Eleanor M. Simonsick; Marilyn S. Albert; Susan M. Resnick; Jennifer A. Schrack (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2023)
Abstract INTRODUCTION White matter hyperintensities (WMHs) increase with age and contribute to cognitive and motor function decline. Energy costs for mobility worsen with age, as the energetic cost of walking increases and energetic capacity declines. We examined the cross‐sectional associations of multiple measures of walking energetics with WMHs in mid‐ to late‐aged adults. METHODS A total of 601 cognitively unimpaired adults (mean age 66.9 ± 15.3 years, 54% women) underwent brain magnetic resonance imaging scans and completed standardized slow‐ and peak‐paced walking assessments with metabolic measurement (V̇O2). T1‐weighted scans and fluid‐attenuated inversion recovery images were used to quantify WMHs. Separate multivariable linear regression models examined associations adjusted for covariates. RESULTS Lower slow‐paced V̇O2 (B = 0.07; P = 0.030), higher peak‐paced V̇O2 (B = –0.10; P = 0.007), and lower cost‐to‐capacity ratio (B = .12; P < 0.0001) were all associated with lower WMH volumes. DISCUSSION The cost‐to‐capacity ratio, which describes the percentage of capacity required for ambulation, was the walking energetic measure most strongly associated with WMHs.